Joseph Roths feuilletons in his understanding, it’s development phases and Roths cooperation with the exile press - Gołaszewski, Marcin (Acta Universitatis Lodziensis. Folia Germanica, 2023)
Joseph Roth (1984–1939) belonged to a generation that was affected by two world wars, the collapse of the old world order, emerging nationalism and forced emigration. Columns, journalistic activity and literary works were an expressions of growing frustration, escape from the world, resignation and one’s own helplessness. The columns are a perfect mirror of the changes that have occured in the writer over the decades. At the same time, they became an expression of emotions and experiences and manifested them in various forms and styles of artistic expression. The definition of the feature section, in the sense Joseph Roth understands, stylistic influences on his work and its characteristic features, cooperation with the exile press are the components of the article understood as an attempt to outline the general characteristics of the genre in the author’s work.